Lewis Acids in Organic Synthesis 2000
DOI: 10.1002/9783527618309.ch7
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Aluminum Lewis Acids in Organic Synthesis

Abstract: The earliest report of a reaction mediated by a chiral three coordinate aluminum species describes an asymmetric Meerwein-Ponndorf-Verley reduction of ketones with chiral aluminum alkoxides which resulted in low induction in the alcohol products [1]. Subsequent developments in the area were sparse until over a decade later when chiral aluminum Lewis acids began to be explored in polymerization reactions, with the first report describing the polymerization of benzofuran with catalysts prepared from and ethylalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 108 publications
0
8
0
Order By: Relevance
“…The Lewis acid properties of organic aluminum compounds are well established in organic chemistry. They are responsible for a plethora of organic reactions, polymerizations, and catalytic cycles . Among those compounds, Lewis acidic derivatives prepared from AlCl 3 are primarily used, although poor selectivity and control of reactivity are often the major issues in using these compounds .…”
Section: Introductionmentioning
confidence: 99%
“…The Lewis acid properties of organic aluminum compounds are well established in organic chemistry. They are responsible for a plethora of organic reactions, polymerizations, and catalytic cycles . Among those compounds, Lewis acidic derivatives prepared from AlCl 3 are primarily used, although poor selectivity and control of reactivity are often the major issues in using these compounds .…”
Section: Introductionmentioning
confidence: 99%
“…Alkylaluminum compounds, which tend to be highly air sensitive, are very important reagents widely employed in organic synthesis, as cocatalysts in olefin polymerization, and as initiators in the ring-opening polymerization (ROP) of cyclic esters or copolymerization of CO 2 and epoxides . Recently, the reactivity and catalytic behavior of alkylaluminum complexes have been extensively reported .…”
Section: Introductionmentioning
confidence: 99%
“…Significant structural and chemical studies have also been reported from the Barron group . A continuing challenge centers on the development of chiral analogues for the synthesis of optically pure compounds . A series of aluminum reagents containing C 2 -symmetric, chiral aryloxides were also synthesized and have been applied to asymmetric Claisen rearrangements, 2 aldol reactions, and aldehyde alkylations.…”
Section: Introductionmentioning
confidence: 99%